Technology Entrepreneurship (ENT 600) ILePy Clasz / Nur Ayunni Mukri - Mukri, Nur Ayunni (2020)
The company offers products that have been innovated from the manual window cleaner by using hand. It makes the product more advanced from before. The design and style of the product is big from before and more stable. Company also offers superior quality and design at a reasonable price. The products, design and finishes will continue to evolve based on consumer trends and demands